(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Student centered learning environment has proven to be a solution and can be met with (i) multi-sensory approach to teaching, (ii) increased student activity, to help student internalize their learning, and (iii) sufficient time to overcome student weaknesses. Within this needs, this study aimed at designing, developing and implementing a new online individualized multimedia instructions (OIMI) framework for engineering communication skills (ECS). The OIMI framework was used to deliver the ECS courses in 2012-2013. The framework was subsequently tested to generate a two-stage model for ECS course. The theoretical framework guided development of a questionnaire to measure all measurement scale in the OIMI model. The questionnaire has three sections to assess (i) Individualized Instruction, (ii) MI and (iii) OL. Overall reliability using Alpha Cronbach test and the Rasch Model analysis together with expert reviews for the content validation, suggested that the questionnaire is reliable and valid to measure OIMI model. Data collected from 166 engineering learners were tested with CFA using AMOS 21.0 to obtain three best-fit measurement models from the three latent variables. Subsequently, the SEM was applied to test the hypotheses. The results showed (i) evidence of a three-dimension measurement model for Individualized Instruction, (ii) evidence of a five-dimension measurement model for MI, (iii) evidence of a four-dimension measurement model for OL, (iv) a strong relationship between OL and MI, (v) a positive relationship between Individualized Instruction and OL, and (vi) a negative relationship between Individualized Instruction and MI.